Hold Relax outperforms Friction in treating De Quervain Syndrome: Hold Relax mengungguli Friction dalam mengobati Sindrom De Quervain - Reza Asefi; Bagas Anjasmara; Soffil Yudha Mulyadi (Universitas Muhammadiyah Sidoarjo, 2024)
This study compared the efficacy of Friction and Hold Relax exercises in alleviating De Quervain syndrome symptoms among smartphone game players. Utilizing a quasi-experimental pre and post-test design with 14 participants in each group, the research found that Hold Relax exercises significantly improved thumb function compared to Friction (p = 0.002). These results highlight the importance of tailored therapeutic interventions for De Quervain syndrome patients, particularly among smartphone game players, and provide valuable insights for optimizing treatment strategies in this population. Highlight: Superiority of Hold Relax: Effective for De Quervain syndrome among smartphone users. Tailored Therapy: Recognizes specific needs of smartphone game players. Clinical Insights: Optimizing treatment strategies for De Quervain syndrome rehabilitation. Keyword: De Quervain syndrome, smartphone game players, therapeutic exercises, Hold Relax, Friction